Seleção de genótipos de Toona ciliata fundamentada nas variações radiais do conteúdo de carboidratos não estruturais na madeira - Araújo, Ana Clara Caxito de (2018)
The occurrence of periods of drought has been increasingly frequent due to climate change, causing the increase in tree mortality and reduction in the productivity in native and planted forest stands. This study aimed to identify a robust and efficient characteristic to be used in the selection of superior genotypes regarding the tolerance to drought by evaluating the stock of non-structural carbohydrates present in the annual growth rings of the Toona ciliata stem. We evaluated five T. ciliata clones cultivated at two sites with different levels of environmental stress. We also verified the magnitude of the annual rainfall and drought that occurred during the cultivation of the multiclonal population at both sites. The contents of starch and sucrose and the increase in basal area (IBA) were quantified for all annual growth rings of the sampled trees. Based on the IBA, we evaluated the resistance, recovery, and resilience of the trees to drought. The wood of trees from the site of greater environmental stress (Cana Brava) presented, on average, lower starch and higher sucrose content, with an average diameter at breast height approximately three times lower than those from the site with favorable crop conditions (Campo Belo). Two clones (XD and XE) presented stable contents of starch stored in the stem between the planting sites. These genetic materials presented the highest diameter growth in Campo Belo and greater survival in Cana Brava. There was a tendency of increase in the contents of starch and sucrose from the older to those most recently formed rings. In Campo Belo, the content of non-structural carbohydrates (NSC) in the annual growth rings presented a negative correlation with the annual rainfall and no significant correlation with the magnitude of the annual drought, whereas in Cana Brava these correlations were significant and negative for all clones. The contents of starch and sucrose were positively correlated with the resistance of the trees to drought in Cana Brava, and the content of starch was inversely proportional to the recovery to drought in Campo Belo. It was impossible to observe a clear relationship between the content of NSC in the wood and the resistance, recovery, and resilience of the trees to drought, but there is evidence that clones that store lower contents of starch in the stem present better growth under suitable growing conditions and greater survival in more limiting environments. Thus, the content of NSC is a characteristic with the potential to be used in Toona ciliata breeding programs. However, the relationship between the radial variation of these carbohydrates in the stem and the adaptation of this species to water stress must be better investigated.